الدلالات ومقاصدها في تفسير الرياض للخروبي - أ.خالد حسين إسماعيل (Aljameai, 2023)
المستخلص:تناول هذا البحث جملة من الدلالات الفقهية والأصولية والتربوية وبيان مقاصدها المستنبطة من سورة النور، من خلال تفسير رياض الأزهار وكنز الأسرار، الذي هو لأحد أبرز علماء ليبيا في القرن العاشر الهجري، الشيخ محمد بن علي الخروبي- رحمه الله- واقتصر الباحث في دراسته على استنباط الدلالات الفقهية والأصولية والتربوية التي أشار إليها الشيخ مُبرِزاً مقاصدها، ومعتمدا في ذلك على المنهجين: الاستقرائي والتحليلي، ومبينا أهم الأحكام الفقهية والأصولية والتربوية المستفادة من هذه الدلالات، ومعرفة الأساليب التي استعملها في عرضه لهذه الدلالات، واختار الباحث دراسة تسعة مواضع، قُسّمَت على ثلاثة مطالب، كل مطلب يحتوي على ثلاثة مواضع، وقد تبين من خلال هذه الدراسة أن المؤلف اعتنى بالجانب الفقهي والأصولي، وفي الوقت نفسه لم يهمل الجانب التربوي، وفي جميع ما ذكرنا تجنب الولوج في مسائل الخلاف.Abstract:This research dealt with a number of jurisprudential, fundamentalist and educational indications and the statement of its intent derived from Surat Al-Nour, through the interpretation of: (Riyad al-Azhar and the Treasure of Secrets), which is for one of the most prominent Libyan scholars in the tenth century AH, Sheikh Muhammad bin Ali al-Kharoubi - may God have mercy on him - and the researcher confined himself to His study is to derive the jurisprudential, fundamentalist and educational indications that the sheikh referred to, highlighting their purposes, and relying in that on the two approaches: inductive and analytical, and indicating the most important jurisprudential, fundamentalist and educational rulings learned from these indications, and knowing the methods he used in presenting these indications, The researcher chose to study nine subjects, divided into three demands, each claim containing three subjects, and it was found through this study that the author took care of the jurisprudential and fundamentalist side, and at the same time he did not neglect the educational aspect, and in all of what we mentioned he avoided entering into issues of disagreement.